(untitled) - Zemansky, Mark Waldo (Aukland, 1981)
The book composes two parts: The first part being devoted to fundamental concepts, design to be core of an introductory course in thermodynamics, and the second part, starting with a chapter on elementary statistical mechanics, designed to enable the teacher to choose those applications which require the use of thermodynamics and statistical mechanics. Part 2 also contains such topics as chemical equilibrium, ideal-gas reactions, phase theory, the third law, fuel cells, thermocouples, blackbody radiation, and negative Kelvin temperatures s two parts: The first part being devoted to fundamental concepts, design to be core of an introductory course in thermodynamics, and the second part, starting with a chapter on elementary statistical mechanics, designed to enable the teacher to choose those applications which require the use of thermodynamics and statistical mechanics. Part 2 also contains such topics as chemical equilibrium, ideal-gas reactions, phase theory, the third law, fuel cells, thermocouples, blackbody radiation, and negative Kelvin temperatures
Keywords: Heat,Thermodynamics